2016
DOI: 10.1002/cjce.22506
|View full text |Cite
|
Sign up to set email alerts
|

Trihalomethanes minimization in drinking water by coagulation/flocculation/sedimentation with natural coagulant Moringa oleifera Lam and activated carbon filtration

Abstract: Water treatment plants are designed to remove turbidity and apparent colour, and produce safe water from a microbiological and chemical point of view. Disinfection is the step responsible for the microbiological security, for which chlorine is the most widely‐used agent, since it can react with organic matter present in raw water to form total trihalomethanes (TTHM), which are harmful to humans. In this context, it is proposed to evaluate the effectiveness of the combined process of coagulation, flocculation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 40 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…It was reported that tannins and polyphenols in M. oleifera have antibacterial properties (Khosravi and Behzadi, 2006;Manguro and Lemmen, 2007). In addition, in the previous works conducted by Ghebremichael, (2007); Santos et al, (2016), the coagulant proteins in MOL extracts diminished the count of E. coli. Williams et al, (2017) study confirmed that there were cationic polypeptide compounds in the MOL extracts that inhibited the fecal bacteria.…”
Section: Fecal-coliform Antibacterial Susceptibility To Molmentioning
confidence: 92%
See 1 more Smart Citation
“…It was reported that tannins and polyphenols in M. oleifera have antibacterial properties (Khosravi and Behzadi, 2006;Manguro and Lemmen, 2007). In addition, in the previous works conducted by Ghebremichael, (2007); Santos et al, (2016), the coagulant proteins in MOL extracts diminished the count of E. coli. Williams et al, (2017) study confirmed that there were cationic polypeptide compounds in the MOL extracts that inhibited the fecal bacteria.…”
Section: Fecal-coliform Antibacterial Susceptibility To Molmentioning
confidence: 92%
“…According to several previous studies, the active components of MOL that are responsible for pH reduction in the treated water samples are the watersoluble and thermo-resistant proteins, and the free fatty acids that exist in the Moringa powders (Baptista et al, 2017;Semanka et al, 2022). In addition, Santos et al, (2016); Nordmark et al, (2018) previously proposed that MOL proteins have a considerable adsorption affinity for destabilizing the particulate dispersions, which lowers the pH level.…”
Section: Turbidity and Ph Measurements Of Treated Water Samplesmentioning
confidence: 99%